IBM UKMK DI BIDANG AKUNTANSI DAN KEUANGAN DESA DI KECAMATAN BUNUT KABUPATEN PELALAWAN PROVINSI RIAU, INDONESIA - Jeni Wardi (Universitas Lancang Kuning, 2017)
The Activity of this Community Service aims to provide counseling on how to improve the understanding and knowledge about the making of proposals and financial statement in credit application to banks, as well as increasing knowledge of financial accounting, that conducted in Desa Sidomukti, district of Bunut, Region of Pelalawan, with participants consisting of housewives who have small business, and his efforts are done with simple management and limited capital. This methods of community service activities using lecture methods, and practices. Lecture method is used to convey material and provided space for question and answer session. Practice is done by making financial report and credit proposal to bank